Crossed-Field Demagnetization of a EuBa2Cu3O7 Coated Conductor with BaHfO3 Nanorods. Issue 1 (July 2021) - Suyama, M; Pyon, S; Iijima, Y; Tamegai, T
Abstract: Superconductors can trap large magnetic fields. However, magnetic fields perpendicular to the trapped field reduces the trapped field effective, which is known as crossed-field demagnetization. Crossed-field demagnetization becomes a problem for the application of stacked magnet. We investigated the crossed-field demagnetization of a EuBa2 Cu3 O7 coated conductor with BaHfO3 nonorods which has large critical current density. When an AC transverse field is applied after the magnetization of the coated conductor, the decay of trapped field was significantly accelerated. However, for the AC field smaller than the full penetration field parallel to the ab -plane, the decay becomes slow enough. All these results suggests that we can apply the stacked magnet for rotating machines if the alternating transverse magnetic field is reduced below the penetration field.